GANDHI: A Thousand Contradictions - Roundtable and Art Workshop. THE EXPERIENCE - Soniya Amritlal Patel (Universitat Autònoma de Barcelona, 2021)
How does a hands-on creative arts workshop and roundtable session unfold amongst a group of erudite academics or aspiring academics? This is subtly unveiled in what turned out to be an unforgettable journey, into the person of Mohandas Gandhi and all his eccentricities.